Enriching High School English Lessons with Global Citizenship Education Using Phenomenon-based Learning - Rebecca Rosario Bercasio; Rutesa A Adornado (RIRAI Publisher, 2023)
This study aimed to develop and validate the Grade 7 English lessons with GCED using phenomenon-based learning (PhenoBL). The local and global phenomena were used in the GCED integration in the lessons. Conducted in a public school in the Philippines during the school year 2019-2020 using the descriptive method and documentary analysis, this study specifically developed a curriculum guide for mainstreaming GCED in Grade 7 English, developed sample phenomenon-based GCED-enriched Grade 7 English lessons, and assessed and analyzed these sample lessons. Data gathering strategies included focus group discussion, a workshop on developing the lessons, collaborative critiquing of the lessons, assessing the lessons by validators, and analysis of the final lessons. A validated researcher-made rubric was used to assess the lessons in terms of appropriateness of GCED integration, relevance to the curriculum, flexibility of GCED integration, and significance of the theme, both the GCED integrated and the phenomenon or phenomena focused in the lesson. Findings indicate that the proposed curriculum guide for the mainstreaming of GCED in Grade 7 English lessons using a phenomenon-based learning approach is highly acceptable while the proposed phenomenon-based GCED-enriched Grade 7 lessons are very good instructional resources for teaching about and for global citizenship. The validators’ feedback improved the phenomenon-based GCED-enriched Grade 7 English lessons. Critical themes and local and global phenomena covered in the lessons are helpful in emphasizing GCED. Recommendations to disseminate and utilize the validated phenomenon-based GCED-enriched lessons and conduct a study to determine the effectiveness of the lessons are forwarded.